Transmembrane segments of complement receptor 3 do not participate in cytotoxic activities but determine receptor structure required for action of Bordetella adenylate cyclase toxin. Issue 3 (21st January 2016) - Wald, Tomas; Osickova, Adriana; Masin, Jiri; Liskova, Petra M.; Petry-Podgorska, Inga; Matousek, Tomas; Sebo, Peter; Osicka, Radim
Abstract : Adenylate cyclase toxin-hemolysin (CyaA, ACT or AC-Hly) of the whooping cough agent Bordetella pertussis penetrates phagocytes expressing the integrin complement receptor 3 (CR3, CD11b/CD18, αM β2 or Mac-1). CyaA translocates its adenylate cyclase (AC) enzyme domain into cell cytosol and catalyzes unregulated conversion of ATP to cAMP, thereby subverting cellular signaling. In parallel, CyaA forms small cation-selective membrane pores that permeabilize cells for potassium efflux, contributing to cytotoxicity of CyaA and eventually provoking colloid-osmotic cell lysis. To investigate whether the single-pass α-helical transmembrane segments of CR3 subunits CD11b and CD18 do directly participate in AC domain translocation and/or pore formation by the toxin, we expressed in CHO cells variants of CR3 that contained artificial transmembrane segments, or lacked the transmembrane segment(s) at all. The results demonstrate that the transmembrane segments of CR3 are not directly involved in the cytotoxic activities of CyaA but serve for maintaining CR3 in a conformation that is required for efficient toxin binding and action. Abstract : Transmembrane segments of the integrin complement receptor 3 are not directly involved in cytotoxic activities of Bordetella adenylate cyclase toxin but determine receptor structure required for toxin action.